2020
DOI: 10.2459/jcm.0000000000001124
|View full text |Cite
|
Sign up to set email alerts
|

Rate of venous thromboembolism and atrial fibrillation in a real-world case series of advanced cancer patients: the CaTEV Study

Abstract: Background Venous thromboembolism is the second leading cause of death in cancer patients and its incidence seems underestimated. In addition, cancer patients have an increased risk of developing atrial fibrillation, which may be the first presentation of cancer itself. The primary aim of this study was to define the incidence of venous thromboembolism (VTE) and atrial fibrillation in a real-word series of advanced cancer patients. Methods We performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Overall, DVT prevalence was higher than PE prevalence in patients with cancer-associated VTE in the present study (2.0% vs. 0.9%), which is consistent with the results of previous studies, showing that DVT was more common than PE (10,12,14). However, Cohen et al (13) showed that PE (53.7%) was more prevalent than DVT (46.3%) in patients with active cancer, a notable difference from the findings of the present study.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Overall, DVT prevalence was higher than PE prevalence in patients with cancer-associated VTE in the present study (2.0% vs. 0.9%), which is consistent with the results of previous studies, showing that DVT was more common than PE (10,12,14). However, Cohen et al (13) showed that PE (53.7%) was more prevalent than DVT (46.3%) in patients with active cancer, a notable difference from the findings of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…The present finding is also similar to that of a previous study, indicating that 57.6% of patients with cancer-associated VTE received oral anticoagulants ( 33 ). However, a recent study showed that only 25.0% of patients with cancer-associated VTE received anticoagulation therapy, and low-molecular-weight heparin (LMWH) remained the most widely used anticoagulant drug among patients with advanced cancer ( 14 ). The difference may be attributed to the patients with advanced cancer having an increased risk of bleeding because of rivaroxaban use ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Venous thromboembolism is the second–most prevalent cause of death in cancer patients. 49 Since THCMA possesses inhibitory effects on both venous thrombosis and tumor proliferation, it has the potential to be developed into a dual-function drug treating cancer patients associated with venous thrombosis.…”
Section: Discussionmentioning
confidence: 99%